MANAJEMEN PEMBELAJARAN BERBASIS ANDROID UNTUK PENINGKATAN MUTU PRAKTIK PEMELIHARAAN MESIN KENDARAAN RINGAN - Abdi, Faizal (Wali Pikir: Journal Of Education, 2023)
The learning process is now progressing very rapidly, especially in the field of technology in the era of the industrial revolution 4.0, therefore there is a need for adaptation to improve learning to use technology such as Diagnostic Trouble Code in vocational high schools whose orientation has a special area of technology expertise. This research uses a qualitative descriptive approach with a case study method. Data collection techniques through observation, interview guidelines and documentation. Based on the results of research conducted regarding Android-based learning using diagnostic trouble code applications implemented in two vocational schools, guided and mentored by teachers who have good competence, it can increase student competence. students can elaborate on the practice of using diagnostic trouble codes easily, this does not require the possibility of opening up opportunities for students to create businesses with independent competitiveness